2019
DOI: 10.1088/1555-6611/ab5587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electron blocking layer configuration on the dynamics of laser diodes emitting at 450 nm

Abstract: In this paper, a theoretical study is presented, analysing the Al x Ga (1−x) N electron blocking layer (EBL) at different Al content and Mg-doping levels for the InGaN-based laser diode (LD) emitting at 450 nm. It is observed that the performance of LDs not only depends on the Al content in the EBL but also on the Mg doping levels in the EBL and the In content in the InGaN waveguide. The optimum selection of AlGaN EBL strongly depends upon the In content in the InGaN waveguide. It is found that, for an In 0.08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In order to reduce electron leakage, people researchers have explored the optimization of the electron barrier. In these studies, researchers confirmed that the Al content in Al x Ga 1−x N EBL can be optimized for suppression of carrier leakage in the quantum well structure [17][18][19]. However, there are few studies on the regulating mechanism of Al content of the AlGaN EBL in various wavelength ranges and its effects on LD performance, resulting in a lack of horizontal comparisons and analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce electron leakage, people researchers have explored the optimization of the electron barrier. In these studies, researchers confirmed that the Al content in Al x Ga 1−x N EBL can be optimized for suppression of carrier leakage in the quantum well structure [17][18][19]. However, there are few studies on the regulating mechanism of Al content of the AlGaN EBL in various wavelength ranges and its effects on LD performance, resulting in a lack of horizontal comparisons and analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to improve the performance of GaN LDs, such as increased output power, decreased threshold current, and enhanced slope efficiency. Improved designs include various electron blocking layers (EBLs) for better suppression of electron leakage [ 7 , 8 , 9 ] and optimization of various waveguide layers (WLs) and cladding layers (CLs) to decrease internal optical absorption losses [ 10 , 11 , 12 ]. There has been less research on the multiple quantum well (MQW) active region of GaN LDs relative to that on GaN-based light-emitting diodes (LEDs) because the LD structure is much more complex.…”
Section: Introductionmentioning
confidence: 99%